1981
DOI: 10.1073/pnas.78.8.4941
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of single crystals of dipalmitoylphosphatidylcholine.

Abstract: Optical birefringence and x-ray measurements are reported for single crystals (0.5 mm x 2 mm X 5 ,m) of dipalmitoylphosphatidylcholine as a function of temperature and relative humidity. Large single crystals grown in CHC1jacetone at a low water concentration undergo an irreversible phase transformation at 20'C and 70% relative humidity or at 60°C and 65% relative humidity. After this transformation occurs, the crystals can be made to undergo a reversible transformation into and out of the L. phase. The x-ray-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Third, the freeze-fracture images (Figures 1 and 2) show regular striations in the hydrophobic interior of the bilayer. Similar striations have been seen in DMPC, DPPC, and DPPG bilayers at pH 8.0 (Luna & McConnell, 1977;McIntosh & Costello, 1981;Watts et al, 1978) and DPPCcholesterol (x < 0.05) bilayers (Lentz et al, 1980). The replicas of hydrophobic fracture faces shown in Figures 1 and 2 do not exhibit lenses of benzene between lipid monolayers.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Third, the freeze-fracture images (Figures 1 and 2) show regular striations in the hydrophobic interior of the bilayer. Similar striations have been seen in DMPC, DPPC, and DPPG bilayers at pH 8.0 (Luna & McConnell, 1977;McIntosh & Costello, 1981;Watts et al, 1978) and DPPCcholesterol (x < 0.05) bilayers (Lentz et al, 1980). The replicas of hydrophobic fracture faces shown in Figures 1 and 2 do not exhibit lenses of benzene between lipid monolayers.…”
Section: Discussionsupporting
confidence: 69%
“…Various lipid samples contained from one to three waters per lipid. In regard to the variation in water content, we note that Urabe et al (1981) have shown that DPPC crystals exposed to atmospheric humidity will rapidly hydrate.…”
Section: Methodsmentioning
confidence: 91%